PENDAMPINGAN PERAN KELUARGA DALAM PEMBENTUKAN IDENTITAS KRISTEN REMAJA - Nainggolan, Jalson; Sitinjak, Komfriska; Manurung, Yuna; Simbolon, Roy Boy (JURNAL BEATITUDES, 2024)
Abstract The purpose of this community service is to socialize and implement mentoring of the role of the family in the formation of adolescent Christian identity. This community service uses the methodology used in this study is a qualitative approach with descriptive analysis. Data were collected through literature studies from various. The results of mentoring the role of the family in the formation of adolescent Christian identity are that the Church, family, and community must work together to create an environment that supports the growth of adolescent faith. By providing the right support, adolescents can develop a strong Christian identity and be able to face existing challenges. Therefore, collaboration between all parties involved in adolescent life is very necessary to ensure that they can live their faith with confidence and responsibility. Keywords: Family, Identity, Adolescents